The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12740/app/106077
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in rhinoplasty applicants, before and after surgery

Abstract: Background: Rhinoplasty surgery is among the most common cosmetic surgeries and patients applying for rhinoplasty comparing to other cosmetic surgeries have more psychological disorders. Present study aims to investigate the mental health in rhinoplasty applicants, before and after Surgery. Materials and methods: This is cross-sectional study conducted on 179 applicants for rhinoplasty in Abadan city during first half of 2018 by using convenience sampling method. The data collection tool was Symptom Checklist-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…22 Results of this study also show that Anxiety was 48% while Depression was 30% in patients seeking rhinoplasty as compared to control group where anxiety was 25% and depression in 19% of patients, but contrary to these results Benjamin Jane in their study have shown higher prevalence of depression (50.6%) as compared to anxiety (32.9) among patients undergoing cosmetic surgery. 23 In the study by Ghahremani et al, it was observed that significant correlation was found among age, gender, marital status and job and that complaints of anxiety and depression was higher among female patients seeking rhinoplasty. 24 Similarly study by Strazdins found significant correlation between age, gender, marital status, occupation and psychological characteristics in patients seeking cosmetic surgery.…”
Section: Discussionmentioning
confidence: 97%
“…22 Results of this study also show that Anxiety was 48% while Depression was 30% in patients seeking rhinoplasty as compared to control group where anxiety was 25% and depression in 19% of patients, but contrary to these results Benjamin Jane in their study have shown higher prevalence of depression (50.6%) as compared to anxiety (32.9) among patients undergoing cosmetic surgery. 23 In the study by Ghahremani et al, it was observed that significant correlation was found among age, gender, marital status and job and that complaints of anxiety and depression was higher among female patients seeking rhinoplasty. 24 Similarly study by Strazdins found significant correlation between age, gender, marital status, occupation and psychological characteristics in patients seeking cosmetic surgery.…”
Section: Discussionmentioning
confidence: 97%
“…It is emphasized in the literature that rhinoplasty was among the most frequently performed aesthetic surgeries, and patients who underwent rhinoplasty had more psychological disorders than in other plastic surgeries. 32 Therefore, individuals with anxiety related to aesthetics and who underwent septorhinoplasty may have psychological issues, which make them experience anxiety more profoundly.…”
Section: Discussionmentioning
confidence: 99%
“…Research carried out by Ghahremani et al indicated that the mantle health of the patient after rhinoplasty showed significant improvement in all dimensions. 3 It was observed that although the purpose of rhinoplasty varies from person to person, the major reason for rhinoplasty is an alteration in appearance. Research studies have shown that the single most motivating factor to perform rhinoplastic surgery is the wish of the patient to change their facial appearance or see a more attractive appearance.…”
Section: Introductionmentioning
confidence: 99%